Use of ontologies for personalized search of knowledge for natural language texts - Rogushina, J.V. (PROBLEMS IN PROGRAMMING, 2018)
The paper analyzes the problems of search personalization of information resources and information objects which is based on the construction and use of user task thesaurus. This thesaurus allows the use of knowledge about search domain and structure of information objects represented by some appropriate ontologies. The definitions of semantic search, its subjects and components allow more articulate issues related to the information retrieval in the Web open environment. Software implementation of the proposed approach confirms the effectiveness of its prac-tical use.Prombles in programming 2016; 1: 73-88